Effects of Different Protein Level Feeds on the Fingerlings Production of Riverine Endangered Notopterus Chitala (Hamilton, 1882) in Ponds (Research in Agriculture Livestock and Fisheries, 2020)
This study was aimed to evaluate the efficiency of three protein level feeds on the fingerlings production of riverine endangered Notopteruschitala (Hamilton, 1882) for a period of two months in ponds. Chital fry (Initial wt, 5.6±0.19 g) were randomly stocked at the rate of 7410 per hector. Feeding trials were conducted under 3 treatments (T1: feed contains 35% protein, T2: feed contains 30% protein, T3: feed contains 25 % protein) each with 3 replications. No significant (P